Perbandingan Sistem Fonologi Bahasa Indonesia dengan Bahasa Kayu Pulau - Suharyanto Suharyanto (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Uniformity is one of several aspects to be achieved through standardization. In the Indonesian context, the achievement of a standard language spoken variety dimensions have some resistance. These barriers, among others, caused by mostly native speakers of Indonesian teak is the local language. Sound system the difference between the Indonesian language with local language bocomes a problem that needs to get attention. This paper will attempt to explain the problem and how to handle it by taking the example of Kayu Pulau language case, a regional language spoken in the city of Jayapura.